Research on the Physio-Biochemical Mechanism of Non-Thermal Plasma-Regulated Seed Germination and Early Seedling Development in Arabidopsis - Cui, Dongjie; Yin, Yue; Wang, Jiaqi; Wang, Zhiwei; Ding, Hongbin; Ma, Ruonan; Jiao, Zhen (Frontiers in Plant Science, 2019)
Non-thermal plasma holds great potentials as an efficient, economical and eco-friendly seed pretreatment method for improving the seed germination and seedling growth, but the mechanisms is still unclear. Therefore, a plant model organism Arabidopsis thaliana was used to investigate the physio-biochemical responses of seeds to non-thermal plasma at different treatment times by measuring the plant growth parameters, redox-related parameters, calcium (Ca2+) level and physicochemical modification of seed surface. The results showed that short-time plasma treatment (0.5, 1 and 3 min) promoted seed germination and seedling growth, whereas long-time plasma treatment (5 and 10 min) exhibited inhibitory effects. The level of superoxide anion (O2•) and nitric oxide (NO) and the intensity of infrared absorption of hydroxyl group were significantly higher in short-time plasma treated Arabidopsis seeds, and the level of hydrogen peroxide (H2O2) were remarkably increased in long-time plasma treated seeds, indicating that O2•, •OH and NO induced by plasma may contribute to breaking seed dormancy and advancing seed germination in Arabidopsis, while plasma-induced H2O2 may inhibit the seed germination. The intensity of hydroxyl group and the contents of H2O2, malondialdehyde and Ca2+ in Arabidopsis seedlings were obviously increased with the plasma treatment time. Catalase, superoxide dismutase and peroxidase activities as well as proline level in short-time treated seedlings were apparently higher than control. The etching effects of plasma on seed surface were dose-dependent, spanning from slight shrinkages to detached epidermis, which also significantly increased the oxidation degree of seed surface. Therefore, the improved activities of antioxidant systems, moderate •OH, H2O2 and Ca2+ accumulation and seed surface modification induced by plasma all contribute to the enhanced seedling growth of Arabidopsis after short-time plasma treatment.